Ethical foundations in religious pluralism: epistemological perspectives for interfaith education in a globalized world - Puspawati, Srirahayu; Arjana, Ida Bagus Made (Indonesian Institute for Counseling, Education and Therapy (IICET), 2025)
Religious pluralism is both a challenge and an opportunity in an increasingly globalized world, especially in the context of interfaith education. Ethical foundations and epistemological perspectives are very important for building inclusive and reflective interfaith dialogue. This study aims to critically analyze the ethical foundations of religious pluralism from an epistemological perspective and their relevance to interfaith education in the era of globalization. The method used is qualitative with a comprehensive literature study approach, involving an in-depth study of philosophical, theological, and related academic research works. The results of the study reveal that the ethical foundations of religious pluralism must be based on the principles of universal humanism, respect for individual epistemic rights, and critical reflection on claims of absolute truth. Effective interfaith education requires a curriculum and pedagogy that integrate these values ​​in an inclusive and dialogical manner, so as to build attitudes of empathy, openness, and multireligious awareness. These findings provide theoretical and practical contributions to the development of religious education that is able to answer global complexity by forming a generation that is able to live side by side in harmony and civilized.